Modelling Stock Market Volatility in India Using Univariate GARCH Models - ACHARYA, Pramath Nath; KALIYAPERUMAL, Srinivasan; MAHAPATRA, Rudra Prasanna (Journal of Advanced Studies in Finance; Vol 10 No 1 (2019): JASF Volume X Issue 1(19) Summer 2019DO - 10.14505//jasf.v10.1(19).06, 2019)
This study examines the volatility pattern of Indian stock market based on the daily price data of National Stock Exchange and Bombay Stock Exchange over the period 1996-2017. The analysis is carried out by using various GARCH models to capture symmetric as well as asymmetric effects. The study suggests the presence of asymmetry and PGARCH model as the best fit model among all the selected models.